ANALYZING THE RELATIONSHIP BETWEEN TRAINING INITIATIVES AND EMPLOYEE PRODUCTIVITY IN SMALL-SCALE INDUSTRIES OF CHANDRAPUR - Pedulwar, Suraj Banduji; Sheikh, Niyaj (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper deals with training has & impact of productivity of employees of small-scale industries of Chandrapur. As businesses compete in a fast-evolving marketplace, robust training is crucial to optimizing employee performance and organizational output. It also discusses training, barriers to implementing training programs, and how training affects the productivity of the workforce. Data were collected from employees and managers of small-scale industries using structured questionnaires, using a quantitative research approach. Descriptive statistics and inferential analysis were used to evaluate the effectiveness of the training interventions. Once trained and developed thus, employees boast of better skills, performance, and productivity, benefitting the organization immensely. But financial constraints, lack of skilled trainers, and resistance to change hinder training implementation. It discusses a number of strategies — government support, technology-enabled learning strategies, specialized training programs — that could help the sector improve workforce building.